2016
DOI: 10.1055/s-0036-1584892
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Orbital Blowout Fractures: Complications and Postoperative Care Patterns

Abstract: Orbital fractures are a common result of facial trauma. Sequelae and indications for repair include enophthalmos and/or diplopia from extraocular muscle entrapment. Alloplastic implant placement with careful release of periorbital fat and extraocular muscles can effectively restore extraocular movements, orbital integrity, and anatomic volume. However, rare but devastating complications such as retrobulbar hematoma (RBH) can occur after repair, which pose a risk of permanent vision loss if not addressed emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
(40 reference statements)
1
14
1
2
Order By: Relevance
“…Outpatient management was significantly more common among those who performed 20 or more OBF repairs annually. 13 Other authors have also argued in support of outpatient repair, although this is not yet considered standard of care in all settings. 3,14 The rate of orbital fractures, and therefore the associated cost of surgical management, is on the rise.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Outpatient management was significantly more common among those who performed 20 or more OBF repairs annually. 13 Other authors have also argued in support of outpatient repair, although this is not yet considered standard of care in all settings. 3,14 The rate of orbital fractures, and therefore the associated cost of surgical management, is on the rise.…”
mentioning
confidence: 99%
“…In a recent study by Shew and colleagues, a survey of AO North America Craniomaxillofacial faculty revealed that out of 105 craniomaxillofacial surgeons, 29% send patients home on the same day of surgery. Outpatient management was significantly more common among those who performed 20 or more OBF repairs annually 13. Other authors have also argued in support of outpatient repair, although this is not yet considered standard of care in all settings 314…”
mentioning
confidence: 99%
“…Orbital fractures cause severe injuries like loss of vision and disfigurement of face, leading to lifelong morbidity. 2 In a study on pediatric ocular trauma reported, eye globe was involved in 76.7%. 3 In another study from 2001 to 2014, 15 pediatric patients were identified as having sustained an NOE fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Complications of oculomotor training have been previously reported, including hemorrhage and suture rupture due to excessive activity. 19 All clinicians should carefully observe the patient during training. For patients with obvious lower eyelid subcutaneous or retrobulbar hemorrhage, eyelid or bulbar conjunctival edema, or difficulty in eyelid opening, the training should be suspended until bleeding subsides.…”
Section: Discussionmentioning
confidence: 99%